CONGENITAL LOBAR EMPHYSEMA IN AN ADULT WITH VSD - DR.S.SAKTHI SELVA KUMAR M.D; DR.M.V.BHARGAVI, M.D; PROF.DR.S.PALANIANDAVAN, M.D (International Journal of Pharma and Bio Sciences, 2015)
Congenital lobar emphysema (CLE) is a clinico-radiological diagnosis, seen usually by four-six weeks of age (50% of patients) and rarely (<5% of patients) after the age of six months. Here, we report a young male, a Known case of VSD presented with fever and cough with expectoration and physical examination revealing the features of right sided pneumothorax. X-ray chest, with subsequent CT-chest, lead to the diagnosis of CLE.. Patient is managed conservatively.